Convergence of Teaching Plans to the Pedagogical Political Project as to teaching methodologies (Research, Society and Development, 2021)
The present study aims at identifying the existing convergence between the 5th-grade Elementary School teaching plans and the Political Pedagogical Project (PPP) related to the teaching methodologies running in a private school at Santa Catarina State. This is a descriptive qualitative research. For data processing, researchers applied the content analysis technique proposed by Bardin (1977). The results showed that, in general, the methodological procedures presented in the teaching plans converged with those established in the Political Pedagogical Project, despite some gaps from some projects not aligned with the school PPP. Evidence showed that some teachers only listed the procedures without clarifying the teaching methods applied.